Análisis de la calidad del curso virtual Objetos de Aprendizaje en Exelearning para Educadores, utilizado por los docentes de la Escuela de Educación Básica Particular Liceo Americano de la ciudad de Loja, año lectivo 2023-2024. - Guachisaca Zhunio, Jakeline Alexandra (2024)
Currently, virtual courses emerge with the aim of strengthening teaching through the quality of topics presented in these settings. For this reason, this research analyzes the quality of the virtual course "Learning Objects in Exelearning for Educators," used by the teachers of the Private Basic Education School Liceo Americano in the city of Loja, for the 2023-2024 academic year. The methodology used is based on the deductive method, descriptive type, with a non-experimental design and a quantitative approach. The population consisted of 16 teachers from the institution, obtaining a sample of 11 collaborating teachers. The research instrument was a structured questionnaire. Subsequently, the virtual course was described from four factors: pedagogical, functional, technological, and temporal, thus allowing the visualization of the parameters contained in each factor, in accordance with the investigated theoretical basis. From the analysis of the obtained data, the parameters with the highest percentage in relation to the dichotomous scale were highlighted. Firstly, the teachers selected the parameter "The topics are well-structured and have a logical order," pertaining to the pedagogical factor. Next, the parameter concerning "The means of communication between participants and tutors" was highlighted, related to the technological factor. Finally, the parameters based on the temporal factor were presented, such as "The time indicated to participate in the discussion forums is sufficient" and "Compared to a fully in-person course, an online course allows you to optimize your time and perform different activities simultaneously." Finally, it was possible to analyze the quality of the virtual course "Learning Objects in Exelearning for Educators," through the use of the questionnaire by the collaborating teachers, showing that the virtual course has a higher percentage in the pedagogical and technological factors, while functional and temporal factors show lower results. Keywords: Quality, Virtual course, Learning objects, Exelearning.